Features of legal regulation of patriotic education of students: regulatory and legal aspects of the «Russia in the World» program - A. A. Aslaeva (Вестник Самарского университета: История, педагогика, филология)
The article explores the features of legal regulation of patriotic education of students: regulatory aspects of the program «Russia in the World». Relevance and novelty. The main goal of the course «Russia in the World» is to develop civic feelings and patriotism among high school students, as well as to instill a clear understanding of national interests of the Russian Federation. This course is uniquely structured to provide a comprehensive understanding of various aspects of life in Russia and to present them in a modern context, which is not offered by any other training program at the moment. Based on the results of the study, a review of scientific and practical information on the formation of the regulatory framework, which is the basis for the preparation of the educational program «Russia in the World» and defines the ideological basis, goals, objectives, structure, learning outcomes formulated in the program. It is necessary to take into account all the recommendations of state documents in the field of patriotic education and upbringing.